Guias práticos de saúde - Harvard Medical School (Sol90, 2014)
1.º vol.: Ansiedade e fobias, 48 p.; 2.º vol..: Problemas cardíacos, 48 p.; 3.º vol.: Diabetes, 48 p.; 4.º vol.: Hipertensão, 48p., 5.º vol.: Colesterol, 48 p.; 6.º vol.: Perder peso, 48 p.;